(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The definitional dictionary uses synonymy or descriptive synonymy to explain words that belong to the verbal group of words and verbs from the outskirts of the functional-semantic field of aspectuality. The process of action and state must be described, together with aspectuality schemes, in order to enhance this interpretation. Finding lexemes that are mutually synonymous is made possible by this interpretation. The depiction of the same process reflects the form and principle of lexicographic interpretation of words. The essay demonstrates the importance of lexical components in verb and adverb explanations.